Philosophers on the Periphery of Ashkenaz : Jewish Intellectual Life and Philosophy in the Czech Lands from the Twelfth to the Fifteenth Century. Officina Philosophica Hebraica Volume 4 - Visi, Tamás (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
Moses Maimonides (1138-1204) had many followers among Jews living in the Mediterranean Basin, but his philosophical books were almost totally ignored by Ashkenazi Jews. Yet, the eastern periphery of Ashkenaz was an exception: in the late fourteenth century a circle of veritable philosophers emerged in the Jewish community of Prague and existed until the end of the Hussite wars (ca. 1434). This book analyses the works of the most important members of the circle, Yom Tov Lipmann Mühlhausen, Avigdor Kara, and Menahem Shalem, and examines the impact of philosophy on Jewish society using Max Weber's sociology and Marc Richir's phenomenology.